Methane Seepage Caused by Gas Hydrate Dissociation in the Mid‐Okinawa Trough Since the Last Glacial Maximum - Ang Li; Nengyou Wu; Qing Li; Zhou Wang; Yizhao Wan; Feng Cai; Zhilei Sun; Dong Feng (Geophysical Research Letters, 2023)
Abstract Submarine methane seepage can potentially be promoted by the dissociation of the marine hydrates surrounding the continental margins due to oceanic warming since the Last Glacial Maximum. This seepage could be archived by authigenic carbonates at seeping sites, but the time lag caused by heat transmission through the sediment column leads to an inconsistency between the ages of the carbonate and the period of bottom water warming. Here we present the records of the authigenic carbonate crust from drilling site D1 in the Mid‐Okinawa Trough. Uranium–thorium dating results show that the carbonate crust mainly grew downwards during 14–6 ka. Gas hydrates hosted in the relatively thin stability zone dissociated in a rapid response to bottom water warming and intensified the methane seepage. Our study better supports the hypothesis that a considerable amount of methane can be released from marine hydrates due to global climatic changes.